AN IMPLEMENTATION OF THAIR AND SHAIWA E-LEARNING KNOWLEDGE MANAGEMENT SYSTEM WITHOUT KNOWLEDGE ORGANIZER - Taiwo, Oloruntoyin Sefiu; Akanni, Adeyemi Abdullahi; Oluwadamilola, Amao Taiwo (Journal of Islam and Science, 2021)
The advent of e-learning has made unlimited source of knowledge available to us all. Recent research reveals great interest to introduce Knowledge Management (KM) ideas to e-Learning systems. It is argued that KM can facilitate an eLearning system. The joint studies of KM and eLearning point out the same fundamental goal: facilitating organizational learning. Researchers try to analyze the similarity of the goals, methods of assessment, and some knowledge sharing processes both in KM and eLearning. An eLearning system within KM is traditionally analyzed as a knowledge resource repository, where the KM methods can be implemented to increase the effectiveness of knowledge dissemination. Researchers have designed many models for integrating knowledge management into e-learning system. Some are practically implemented while some are not practically implemented. Despite these various models, researchers are still working for more interactive, efficiency and effective model that can be used to quickly identify the most relevant information (knowledge) and distribute it to meet specific needs. This work investigates the integration of e-Learning systems and Knowledge Management technology to improve, capture, organize and deliver large amounts of knowledge. First, a model is proposed for the phases of knowledge management. The model is then enhanced with concepts and technology from e-Learning. The model is then used to illustrate real world scenarios that add increasing amounts of knowledge management to an e-Learning environment. The system, AMID promises high interactivity, efficiency and effectiveness of integration of knowledge management and e-learning. In addition, the developed system will enhance technical learning process.